Communicating physical activity messages with adolescents: what works? A scoping review with stakeholder consultation - Grady, Caera L.; Murtagh, Elaine; Ng, Kwok; Bengoechea, Enrique Garcia; Woods, Catherine B. (BMC, 2025)
Background Global levels of adolescents' physical inactivity are cause for concern, despite the well-documented health benefits of physical activity (PA). Addressing the messaging of PA is one approach to improve PA knowledge. While increased knowledge does not necessarily lead to behavior change, physically active students have better knowledge of the health benefits of PA. Recently, researchers have highlighted the need for an effective communication strategy for PA messages. This review aimed to summarize the state of the available evidence about the operationalization of communicating PA messages, the evaluation, and effectiveness of PA messages.
Methods The Levac six steps and Joanna Briggs Institute methodological guidance for scoping reviews were followed. Five databases were searched up until April 8th 2024. Both title and abstract and full-text screening were piloted whereby 10% of the total articles were double-screened and the remainder were completed by CG. Data were extracted and a data-based convergent synthesis design was used following qualitative synthesis methods. Finally, a consultation with key stakeholders was held to confirm the findings concerning practical relevance.
Results A total of 19,412 articles were identified from searches, 94 full texts were included in the final analysis, corresponding to 80 individual studies. The evidence confirms that there are many factors to consider when communicating PA messages and evaluating their effectiveness. Inconsistencies exist regarding the timing and frequency of message delivery and the evaluation of effective communication. When communicating PA with adolescents, messages commonly focus on the benefits of PA and strategies to overcome barriers and are commonly delivered in the school setting by researchers or school stakeholders i.e. teachers, peers. Messages should be concise, positively framed, support adolescent autonomy, and utilize different messaging platforms and techniques to avoid staleness.
Conclusions There is a lack of a standardized approach to communicating PA messages with adolescents making evaluation and comparison challenging. Future research should focus on developing guidance to facilitate the effective communication of PA messages with adolescents.